The Influence of Artificial Intelligence on Student’s Intention to Commit Academic Fraud with Family Culture as a Moderating Variable - Irsutami, Irsutami; Halim, Dzaki (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The purpose of this study is to examine the influence of artificial intelligence on students' intention to commit academic fraud, with family culture moderating the effect of artificial intelligence on this intention. Data were collected using questionnaires distributed both online and offline, with a sample of 120 accounting students from four universities in Batam City. The analysis used descriptive statistics. The results of the study indicate that artificial intelligence has a positive influence on students' intention to commit academic fraud, and that family culture strengthens the effect of artificial intelligence on this intention.